Youth Kicker's Knee: Lateral Distal Femoral Hemiphyseal Arrest Secondary to Chronic Repetitive Microtrauma. (August 2019) - Dempewolf, Michael; Kwan, Kevin; Sherman, Benjamin; Schlechter, John A.
Abstract : Year-round competitive sports place the youth athlete at risk for injury from chronic repetitive stress. Stress injuries to the distal femoral physis in adolescents are rare. This report highlights three male youth soccer players who presented with a lateral distal femoral hemiphyseal arrest and a subsequent unilateral genu valgum deformity in their dominant "kicking leg" due to repetitive microtrauma, a phenomenon we refer to as youth kicker's knee. Mean age was 14.2 years, and all participated in year-round soccer and American football. Imaging demonstrated aberration of the distal lateral femoral physis. All patients were surgically treated. Our series illustrates a unique presentation of a chronic overuse injury in hyper sporting adolescents resulting in an ipsilateral genu valgum deformity. Understanding adolescent growth and developmental characteristics is paramount to appropriate care, prevention, and treatment of physeal injuries that may occur from repetitive overuse and avoid surgery in these young athletes when possible.